EDUKASI DAN PRAKTIK PERTOLONGAN PERTAMA CEDERA OLAHRAGA BAGI SISWA SMA OLAHRAGA - Afifah Cahayani Adha; Marliana; Alfitri Yana Yunita yana (LPPM Universitas Awal Bros, 2026)
Sports injuries are a common risk faced by high school students, especially in sports-focused schools, due to high training and competition intensity. The main problem is the lack of knowledge and practical skills in providing appropriate first aid, which can potentially worsen injuries and delay recovery. This Community Service (PkM) activity aims to enhance the competence of students at SMA Olahraga Pekanbaru through education and practical training in sports injury first aid. The method used is an interactive workshop combining theoretical presentation (covering RICE/POLICE principles, identification of common injuries) with hands-on simulation practice (such as bandaging and immobilization techniques) using props. The target participants are 20 students from various sports. Expected outcomes include increased participant knowledge and skills (measured through pre-test and post-test), as well as supporting products such as training modules, documentation videos, and a scientific article. This activity is expected to foster a culture of sports safety and reduce the negative impact of improperly managed injuries.